2017
DOI: 10.1093/pubmed/fdx168
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of outcomes for patients with common mental health disorders receiving psychological therapies in community settings: a systematic review

Abstract: We identified key predictors for recovery in a community settings from five countries. The evidence currently available for this setting is limited, so this review serves as a starting point to highlight key factors that warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…In a systematic review investigating social anxiety disorder, Mululo, de Menezes, Vigne, and Fontenelle (2012) found that early onset, greater severity, and comorbidity resulted in less favorable treatment outcomes. The finding related to comorbidity is congruent with other reviews investigating predictors of treatment outcomes that have found comorbid depression is related to poorer treatment outcomes (Amati, Banks, Greenfield, & Green, 2017;Eskildsen, Hougaard, & Rosenberg, 2010). An additional review by Vall & Wade (2015) found that lower motivation significantly related to dropout (r=.23) and fewer familial problems related to a more favorable overall outcome (r=.36).…”
Section: Future Directionssupporting
confidence: 86%
“…In a systematic review investigating social anxiety disorder, Mululo, de Menezes, Vigne, and Fontenelle (2012) found that early onset, greater severity, and comorbidity resulted in less favorable treatment outcomes. The finding related to comorbidity is congruent with other reviews investigating predictors of treatment outcomes that have found comorbid depression is related to poorer treatment outcomes (Amati, Banks, Greenfield, & Green, 2017;Eskildsen, Hougaard, & Rosenberg, 2010). An additional review by Vall & Wade (2015) found that lower motivation significantly related to dropout (r=.23) and fewer familial problems related to a more favorable overall outcome (r=.36).…”
Section: Future Directionssupporting
confidence: 86%
“…Contrary to our findings, a systematic review on the predictors of recovery in people with CMDs in commmunity settings, in high-income countries found that socio-economic status did not have a direct impact on treatment outcome. However, the same review also found evidence that socioeconomic status had an impact on baseline depression scores, which is itself a predictor of outcome (Amati et al ., 2017). The evidence on the impact of socioeconomic status on mental health outcomes between low- and middle-income countries and high-income countries, do not always align.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that the male gender was associated with a higher GAD-7 score reduction, compared to females. In contrast, a systematic review on the predictors of treatment outcome for people with CMDs, found that being female was associated with positive treatment outcomes for patients receiving psychological therapies in high-income countries (Amati et al ., 2017). Similarly, a study investigating the effectiveness of collaborative care for anxiety when compared to usual care found that women who received collaborative treatment showed clinical improvements, while no differences were found for men.…”
Section: Discussionmentioning
confidence: 99%
“…Models of mental health recognize that mental health is influenced by individuals (eg, symptoms), social (eg, work stress), and environmental (eg, access to service and injustice) factors [15]. At the individual level, those involved with ICs may have greater symptom severity, which has been associated with poorer treatment outcomes [16]. Specifically, ICs often have requirements for the severity or duration of symptoms before a disability claim can be granted, especially long-term disability, which may contribute to more severe symptoms in IC groups [17].…”
Section: Outcomes In Insurance Company Clientsmentioning
confidence: 99%
“…The Patient Health Questionnaire-9 (PHQ-9) [31] is a 9-item validated self-report questionnaire that is used to assess depression symptom severity. Total scores range from 0 to 27 with scores being interpreted as indicative of mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19), and severe (20)(21)(22)(23)(24)(25)(26)(27) depressive symptoms [32]. A cut-off score of 10 or higher is used to identify those who are likely to have a diagnosis of depression [20].…”
Section: Patient Health Questionnaire 9-itemmentioning
confidence: 99%